FLUID REGIME AND ORIGIN OF GOLD-BEARING RODINGITES FROM THE KARABASH ALPINE-TYPE ULTRABASIC MASSIF, SOUTHERN URAL - Murzin V.V.; Shanina S.N. (My University, 2007)
The rodingites of the Karabash Massif are distinguished by the presence of native cupriferous gold. This zonal hydrothermal-metasomatic complex was formed in three stages. The inner zone of rodingite proper is made up of chlorite-andradite-diopside rocks of stage 1, which are cut by diopside veinlets of stage 2 and calcite veinlets of stage 3. The intermediate zone consists of chloritolites, which give way to the antigorite and chrysotile-lizardite serpentinites of the outer zone. Thermometric and cryometric studies and gas chromatography showed that the gold-bearing rodingites of stages 1 and 2 were formed at t = 420–470°C, P = 2–3 kbar, and XCO2=0.001–0.02, i.e., under conditions typical of rodingite formation. The final stage was accompanied by a decrease in P-T parameters (0.5–1.0 kbar and 230–310°C) and an increase in XCO2 up to 0.04. The rodingite-forming fluid was extremely rich in water (XH2O= 0.942–0.981) and contained hydrogen as the major gas component (XH2 =0.012–0.023); its composition was essentially chloride-magnesium with minor amounts of CaCl2 and FeCl2 and a low salinity of 2.6–8.0 wt % NaCl equiv. The rodingite minerals showed the following isotopic characteristics (‰): δ18O from 5.5 to 6.6 and δD from 42.8 to −44.3 for chlorite, δ180 from 2.0 to 3.8 for andradite, δ18O from 6.0 to 6.6 for diopside, and δ18O from 10.6 to 11.4 and δ13C from 0.1 to −1.8 for calcite. The chloritolite is characterized by δ18O from 5.9 to 6.6 and δD from −49.8 to −64.4; the antigorite serpentinite shows δ18O=6.5 and δD=−65.2; and the antigoritized chrysotile-lizardite serpentinite shows δ18O from 6.8 to 6.9 and δD from −127 to −128. The calculated isotopic composition of fluid in equilibrium with various rocks suggested its metamorphic origin. It was formed from the water released during dehydration of oceanic serpentinites, from the components of ultrabasic and basic magmatic rocks, and, at the final stage, from marine carbon.